Care Coordination for Cognitively Impaired Older Adults and Their Caregivers - Naylor, Mary D. (2007)
Dementia and delirium, the most common causes of cognitive impairment (CI) among hospitalized older adults, are associated with higher mortality rates, increased morbidity and higher health care costs. A growing body of science suggests that these older adults and their caregivers are particularly vulnerable to systems of care that either do not recognize or meet their needs. The consequences can be devastating for these older adults and add to the burden of hospital staff and caregivers, especially during the transition from hospital to home. Unfortunately, little evidence exists to guide optimal care of this patient group. Available research findings suggest that hospitalized cognitively impaired elders may benefit from interventions aimed at improving care management of both CI and co-morbid conditions but the exact nature and intensity of interventions needed are not known. This article will explore the need for improved transitional care for this vulnerable population and their caregivers.